TRANSLANGUAGING METHOD IN CREATIVE WRITING TEACHING - Andayani, Ambar; Retnaningdyah, Pratiwi; Mustofa, Ali; Setiawan, Slamet (Universitas Muhammadiyah Semarang, 2024)
Creative writing teaching is challenging since teachers should facilitate students to use their imagination creatively and to produce it in the form of poetry, prose or drama writing. Translanguaging method in foreign language teaching, which allows students to use other language beside the target language is a strategic way to make students to express their imagination without pressure and at once to gain students’ awareness of creativity by appreciating students’ linguistic repertoire. The present study is experimental research which investigates translanguaging practice in creative writing teaching especially poetry writing. Conducted in a private University in Surabaya, the participants consist of 20 students from the sixth semester which are divided into two classes, 10 students are in control class (conventional treatment) and 10 students in experimental class (translanguaging practice). This research uses mix-methodology, by using quantitative method to know the result of poetry writing score of the students and qualitative method to do in-depth interview to students from translanguaging class. The result shows that the score of poetry writing of the students in translanguaging class are higher than those who are from the control class and the students feel enjoy with translanguaging in the poetry writing class.